Mediation of archival information through the Web - Lima de Carvalho, Milena Carla (Revista General de Información y Documentación, 2023)
This article aims to contribute to an analysis of the level of the Websites of the Portuguese District Archives and equivalent (ADs), an assessment based on the perspectives of users and archive professionals, namely on aspects of the functionality, accessibility and interaction of these websites, thus rectifying an existing gap in the literature on this subject. For this purpose, the Quadripolar Method was adopted, complemented by criteria based on two central references: CONARQ and DLGAB. The process began with a review of the existing literature on Web mediation in about 24 ADs and equivalent in Portugal (Aveiro, Beja, Braga and University of Minho, Bragança, Castelo Branco, University of Coimbra, Guarda, Alfredo Pimenta – Guimarães, Évora, Leiria, Lisbon, Portalegre, Porto, Santarém, Setúbal, Viana do Castelo, Vila Real, Viseu, Madeira, Angra do Heroísmo, Ponta Delgada, Horta, Torre Tombo) and a methodology of action was implemented consisting of online surveys sent to 595 users. The objective of this study was to diagnose the level of interactivity of ADs based on the perceptions of the users surveyed, in order to know to what extent the Internet brings new potentialities in the mediation of ADs’ information.